The Drosophila tctex-1 Light Chain Is Dispensable for Essential Cytoplasmic Dynein Functions but Is Required during Spermatid Differentiation - Li, Min-gang (The American Society for Cell Biology, 2004)
Variations in subunit composition and modification have been proposed to regulate the multiple functions of cytoplasmic dynein. Here, we examine the role of the Drosophila ortholog of tctex-1, the 14-kDa dynein light chain. We show that the 14-kDa light chain is a bona fide component of Drosophila cytoplasmic dynein and use P element excision to generate flies that completely lack this dynein subunit. Remarkably, the null mutant is viable and the only observed defect is complete male sterility. During spermatid differentiation, the 14-kDa light chain is required for the localization of a nuclear “cap” of cytoplasmic dynein and for proper attachment between the sperm nucleus and flagellar basal body. Our results provide evidence that the function of the 14-kDa light chain in Drosophila is distinct from other dynein subunits and is not required for any essential functions in early development or in the adult organism.